2021
DOI: 10.1101/2021.01.04.21249198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

T cell Homeostatic Imbalance in Placentae from Women with HIV in the absence of Vertical Transmission

Abstract: BackgroundImplementation of Option B+ antiretroviral therapy (ART) has significantly lowered vertical transmission rates but has also increased numbers of HIV-exposed uninfected children (HEU), who remain vulnerable to morbidities. Here, we investigated whether altered immune status in HEU originates in the placenta.MethodsWe analyzed T cells from term placentae decidua and villous tissue and paired cord blood from pregnant women living with HIV (PWLWH) who initiated ART late in pregnancy (n=21) with HIV negat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…It is now wellestablished that acute HIV infection is associated with expansion of the effector systemic CD8+ T cell pool and although these cell numbers decline slightly following the initiation of antiretroviral therapy (ART), they remain elevated in most individuals even after years of treatment (107,108). A similar occurrence is noted in the decidua, as it has been recently shown that decidual CD8+ T cells are increased in placentae from women with HIV at term and these proportions correlate with maternal viral load pre-ART (15). Women with high viral loads prior to ART initiation are more likely to have increased CD8+ T cells in the maternal decidua at delivery.…”
Section: Cd8+ Effector T Cellsmentioning
confidence: 97%
See 3 more Smart Citations
“…It is now wellestablished that acute HIV infection is associated with expansion of the effector systemic CD8+ T cell pool and although these cell numbers decline slightly following the initiation of antiretroviral therapy (ART), they remain elevated in most individuals even after years of treatment (107,108). A similar occurrence is noted in the decidua, as it has been recently shown that decidual CD8+ T cells are increased in placentae from women with HIV at term and these proportions correlate with maternal viral load pre-ART (15). Women with high viral loads prior to ART initiation are more likely to have increased CD8+ T cells in the maternal decidua at delivery.…”
Section: Cd8+ Effector T Cellsmentioning
confidence: 97%
“…In addition to these robust immune responses in early pregnancy, the uptake of maternal antiretroviral therapy (ART) has been shown to significantly reduce the risk of vertical transmission, even if taken in the third trimester ( 45 ). However, even in the absence of vertical transmission, maternal HIV infection is associated with an altered immune landscape in the decidua and villous tissue ( 15 ). In addition, placentae from women with HIV have been shown to have increased features of placental insufficiency including maternal vascular malperfusion, and features of acute and chronic inflammation ( 12 ).…”
Section: Hiv Infection At the Maternal Fetal Interfacementioning
confidence: 99%
See 2 more Smart Citations